Television Viewing Behaviour Among Indian Kids - Mittal, Manish (Indian Journal of Marketing, 2008)
Children in India have become most influential agents in the family purchase decisions and television the most popular medium to communicate with them. It is therefore important to understand their television viewing habits to enable marketers and advertisers reach out to them in a better way. This study focuses on understanding the television viewing behaviour of Indian kids. The research indicates that television watching is the most favourite activity among kids and they prefer watching television over playing, reading, socializing and studying but they do not like watching advertisement on television. Average television viewing time varies from 1.20 hours (School days) to 2.47 (Non - school days). Manish Mittal